Interpreting the Onomatopoeia in Javanese Language: The Yowis Ben Comic by Bayu Skak Case - Nabila Shafa Annisa; Widhyasmaramurti Widhyasmaramurti (Institut Seni Indonesia Yogyakarta, 2025)
This study analyzes comics as a visual art medium that communicates meaning through the interaction between images and text. The specific form of this interaction can be seen in the use of onomatopoeia. Onomatopoeia in comics uses pictures as representations of sensory experiences to overcome the limitations of word use. Through pictures, onomatopoeia not only means the imitation of sounds, but also creates impressions, such as emotions or attitudes. This study aims to interpret the meaning of onomatopoeia accompanied by images in the comic Yowis Ben: Lika-liku Anak Band (YBLAB) karya Bayu Skak. The research used a descriptive qualitative method with the onomatopoeic categorization theory of Thomas & Clara (2004), and the onomatopoeic continuum theory of Sasamoto (2019). According to Thomas & Clara’s (2004) framework, the findings of this research show that there is one imitation word for animal sounds (Call of Animals), two imitation words for natural sounds (Sounds of Nature), four imitation words for human sounds (Sounds by Human), and six imitation words for various sounds (Miscellaneous Sounds). In addition, based on the continuum theory from Sasamoto (2019), it was found that, images in comics make the word onomatopoeia, which is an imitation of sound, experience a narrowing of meaning by making it more specific through the appearance of the meaning of impressions, the meaning of feelings, the details of events or events, and the intensity of events.